2001
DOI: 10.2494/photopolymer.14.583
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluoropolymers for Use in 157nm Lithography.

Abstract: Unexpectedly good UV transmittance at 157 nm of poly(norbornene sulfone) bearing a pendant hexafluoroisopropanol functionality has prompted us to employ this fluoroalcohol as an acid group for the design of chemical amplification resists for use in 157 nm lithography. The backbone structures to which the hexafluoroalcohol group is attached are polynorbornene and polystyrene. Furthermore, our discovery that poly(methyl a-trifluoromethylacrylate) is adequately transparent at 157 nm has led us to incorporate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Although the a-trifluorination of PMMA significantly decreases the absorption at 157 nm as reported by Brodsky et al [7] and Ito et al [18,19], the calculated absorptions of (c) and (d) are only 20-30 % smaller than those of (a) and (b). For estimating absorbance in the solid state, calculated oscillator strengths should be divided by molecular volume.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the a-trifluorination of PMMA significantly decreases the absorption at 157 nm as reported by Brodsky et al [7] and Ito et al [18,19], the calculated absorptions of (c) and (d) are only 20-30 % smaller than those of (a) and (b). For estimating absorbance in the solid state, calculated oscillator strengths should be divided by molecular volume.…”
Section: Methodsmentioning
confidence: 60%
“…Figs. 2, 4, and 11 demonstrate the effectiveness of the judicious introduction of -CF3 group and support the good transparency of poly(MTFMA) at 157 nm [18,19]. Fig.12 shows the calculated spectra of the esters of propionic acid (a-d) and 3,3,3-trifluoropropionic acid (e-h).…”
Section: Calculation Of Photoabsorption Spectra Of Model Compounds Fomentioning
confidence: 99%
“…The HFA group can be attached to styrene (St) and norbornene (Nb). 4- (1,1,1,3 [1]. We found that vinyl sulfonyl groups exhibited extremely high transparency at 157 nm and reported that copolymers with HFASt worked as resists [9,10].…”
Section: Introductionmentioning
confidence: 82%
“…Thus, fluoropolymers have been intensively studied because of their high transparency at 157 nm [1][2][3][4][5][6]. In addition to good transparency, the most important property for high-resolution capability is good dissolution characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most research groups investigated fluoropolymers as photoresist materials for F 2 lithography because they are fairly transparent in the vacuum ultraviolet (VUV). [1][2][3][4][5][6] In our recent paper, we demonstrated the synthesis and characterization of fluorine-containing polymers by the polyaddition of fluorine-containing bis(epoxide)s with fluorine-containing dicarboxylic acids, diols, 7 and active diesters. 8 The refractive indices of the obtained polymers decreased when the fluorine contents increased.…”
mentioning
confidence: 99%